Poly(L-lactic acid)/poly(ethylene oxide) based composite electrospun fibers loaded with magnesium-aluminum layered double hydroxide nanoparticles - Ozturk, Esra Altay; Ege, Zeynep Ruya; Murat, Semiha; Erdemir, Gokce; Kuruca, Serap; Erkmen, Ziya Engin; Duygulu, Ozgur; Gunduz, Oguzhan; Caykara, Tuncer; Eroglu, Mehmet S. (ELSEVIER, 2022)
Two types of Mg-Al layered double hydroxide nanoparticles, Mg-Al LDH, at Mg:Al ratio of 2:1 and 3:1were prepared and used as inorganic fillers to improve the mechanical properties of poly(lactic acid)/poly(ethylene oxide) (PLA/PEO) electrospun composite fibers. Their detailed structural characterization was performed using X-ray diffraction (XRD) and transmission electron spectroscopy (TEM) techniques. Spectroscopic, thermal, me-chanical, and morphological properties of the electrospun composite fibers, and cell proliferation on their sur-face, were examined. XRD and TEM analyses showed that the LDH nanoparticles were 50 nm in size and the Mg: Al ratio did not affect the average spacing between crystal layers. Fourier transform infrared (FTIR) and thermal analyses (TA) revealed the compatibility of the filler and the polymer matrix. The nanoparticles considerably improved the mechanical properties of the electrospun mats. The tensile strength and elongation at break values of the composite samples increased from 0.22 MPA to 0.40 MPa and 12.2 % to 45.66 %, respectively, resulting from the interaction between LDH and the polymer matrix. Scanning electron microscopy (SEM) and MTT an-alyses demonstrated that the electrospun composite fibers supported the SaOS-2 cells attachment and prolifer-ation on the fiber surfaces, along with their suitable cytocompatibility.
Keywords: PLA; PEO electrospun mat; Mg-Al LDH; POLY(ETHYLENE OXIDE); SILICATE NANOCOMPOSITES; POLY(LACTIC ACID); MOLECULAR-WEIGHT; BLENDS; CRYSTALLIZATION; Biochemistry & Molecular Biology; Chemistry; Polymer Science